Delivery systems for siRNA drug development in cancer therapy - Cong-fei Xu; Jun Wang (Elsevier, 2015)
Since the discovery of the Nobel prize-winning mechanism of RNA interference (RNAi) ten years ago, it has become a promising drug target for the treatment of multiple diseases, including cancer. There have already been some successful applications of siRNA drugs in the treatment of age-related macular degeneration and respiratory syncytial virus infection. However, significant barriers still exist on the road to clinical applications of siRNA drugs, including poor cellular uptake, instability under physiological conditions, off-target effects and possible immunogenicity. The successful application of siRNA for cancer therapy requires the development of clinically suitable, safe and effective drug delivery systems. Herein, we review the design criteria for siRNA delivery systems and potential siRNA drug delivery systems for cancer therapy, including chemical modifications, lipid-based nanovectors, polymer-mediated delivery systems, conjugate delivery systems, and others.